A Comparative Study of Geometry in Elementary School Mathematics Textbooks from Five Countries - Der-Ching Yang; Tzu-Ling Wang (Lectito Journals, 2016)
The purposes of this study were to compare the differences in the use of geometry in elementary school mathematics textbooks among Finland, Mainland China, Singapore, Taiwan, and the USA and to investigate the relationships between the design of the textbooks and students' performance on large-scale tests such as TIMSS-4 geometry, TIMSS-8 geometry, and PISA space and shape. The content analysis method was used to collect data, and then chi-square tests and correlation analyses were used to analyze data. The results showed that there were significant differences in representation form, problem type, and question format among these mathematics textbooks from the five countries. Moreover, the strength of the positive relationships between visual form (combined form) and students' performance on TIMSS-4 geometry, TIMSS-8 geometry, and PISA space and shape decreases as students advance to higher grades, whereas increasing strength of correlations as students get older is found between contextual problems and students' performance on the three large-scale tests.